Design of spherically structured 3D in vitro tumor models -Advances and prospects - Ferreira, L P (2019)
Three-dimensional multicellular tumor models are receiving an ever-growing focus as preclinical drug-screening platforms due to their potential to recapitulate major physiological features of human tumors in vitro. In line with this momentum, the technologies for assembly of 3D microtumors are rapidly evolving towards a comprehensive inclusion of tumor microenvironment elements. Customized spherically structured platforms, including microparticles and microcapsules, provide a robust and scalable technology to imprint unique biomolecular tumor microenvironment hallmarks into 3D in vitro models. Herein, a comprehensive overview of novel advances on the integration of tumor-ECM components and biomechanical cues into 3D in vitro models assembled in spherical shaped platforms is provided. Future improvements regarding spatiotemporal/mechanical adaptability, and degradability, during microtumors in vitro 3D culture are also critically discussed considering the realistic potential of these platforms to mimic the dynamic tumor microenvironment. From a global perspective, the production of 3D multicellular spheroids with tumor ECM components included in spherical models will unlock their potential to be used in high-throughput screening of therapeutic compounds. It is envisioned, in a near future, that a combination of spherically structured 3D microtumor models with other advanced microfluidic technologies will properly recapitulate the flow dynamics of human tumors in vitro.